(untitled) (Annals of Medical Research, 2021)
Aim: In a sample of the Turkish population, we aimed to evaluate differences in hard palate asymmetry by sex, the direction of right-left dominance, and how hard palate asymmetry and morphometric measurements are shaped with age.Materials and Methods: The present study was conducted on 3-dimensional computed tomography images of the head and neck region belonging to 172 (88 males, 84 females) individuals aged between 20-89 years. In this study, the distances between the Incisive foramen-Greater palatine foramen, Greater palatine foramen-Posterior nasal spine on the right and left sides with regard to the hard palate were measured. The asymmetry ratio was determined as a percentage using the asymmetry index. Furthermore, the angle values between the Incisive foramen-Posterior nasal spine-Greater palatine foramen on the right and left sides were measured on the lines between the measured points and compared with each other.Results: The measured parameters were compared between sexes, higher linear measurement parameters were found in males; angular values and the asymmetry index were close to each other, and no difference was found between them. When a comparison was made between the sides, the difference was revealed only in the measurement of the Greater palatine foramen-Posterior nasal spine, and the right side was larger. In all cases, the right side was larger in 79 cases in the Incisive foramen-Greater palatine foramen asymmetry index, and in 93 cases, the asymmetry was to the left. In the Greater palatine foramen-Posterior nasal spine asymmetry index, it was found that the asymmetry was to the right in 61 cases, and the asymmetry was to the left in 111 cases. Conclusion: This study provided important data on the hard palate morphology of the Turkish population. It also presented anthropological references for hard palate measurements of the Turkish population. Using 3-dimensional computed tomography images, we determined the greater palatine foramen’s location according to the posterior nasal spine and incisive foramen. Determining the greater palatine foramen’s location according to anatomical structures will contribute to determining the location of the greater palatine foramen in surgical interventions to be performed in this region.